THE STRATEGY OF ONLINE MARKETING AT Mc. DONALD'S RESTAURANT TO INCREASING SALES IN THE DIGITAL ERA - Kusuma, Aria Cendana; Mukhlis, Ahmad; Fatari, Fatari (Yayasan Education and Social Center, 2024)
One of the essential foundations in the digital business era is online marketing, which uses internet platforms such as websites, social media, and online advertising to reach target audiences effectively, expand brand reach, and increase sales volumes in a market that is becoming increasingly connected and competitive. Within the context of the digital era, this research aims to investigate the online marketing strategies McDonald's Restaurant has implemented to boost sales. In the context of online marketing strategy, the primary focus of the research is on the segmentation, targeting, product positioning, and mixing strategies associated with online marketing. The purpose of this research is to investigate the difficulties encountered when implementing and promoting sales strategies and online marketing strategies using a qualitative approach. Collecting primary data through interviews and secondary data from documents and newspapers are both methods utilized in research. According to the research findings, successful online marketing has the potential to increase sales volume significantly. This research provides valuable insight into practical methods to improve sales performance by implementing integrated online marketing strategies, strengthening brand positioning, identifying market opportunities, and overcoming challenges in a dynamic and changing business environment. This research analyzed strengths, weaknesses, opportunities, and threats (SWOT)